Computational Strategies for the Architectural Design of Bending Active Structures. Issue 3 (September 2013) - Nicholas, Paul; Tamke, Martin
Active bending introduces a new level of integration into the design of architectural structures, and opens up new complexities for the architectural design process. In particular, the introduction of material variation reconfigures the design space. Through the precise specification of their stiffness, it is possible to control and pre-calibrate the bending behaviour of a composite element. This material capacity challenges architecture's existing methods for design, specification and prediction. In this paper, we demonstrate how architects might connect the designed nature of composites with the design of bending-active structures, through computational strategies. We report three built structures that develop architecturally oriented design methods for bending-active systems using composite materials. These projects demonstrate the application and limits of the introduction of advanced engineering simulation into an architectural workflow, and the extension of architecture's existing physics-based approaches.